Turning the tables towards gender inclusivity in entrepreneurial ecosystems - Isakova, Elina; Stroila, Iulia (Journal of business research, 2025)
Although women entrepreneurs significantly contribute to economic and social progress, entrepreneurial ecosystems remain largely shaped by male-oriented approaches that insufficiently address women’s needs. As a result, gender inequality in entrepreneurship persists, with women facing barriers to starting businesses, securing funding, and accessing networks. Drawing on Giddens’ (1984) theory of structuration, we explore how the cultural, social, and material attributes of entrepreneurial ecosystems interact to influence gender inclusivity. Through in-depth interviews with a diverse range of ecosystem actors, we demonstrate how entrepreneurial DNA, a tight-knit entrepreneurial community, and munificent state infrastructure function as structures that both constrain and enable women entrepreneurs. In response, women act as agents, reshaping these structures through advocacy and solidarity. This study contributes to research on entrepreneurial ecosystems by revealing how ecosystem attributes can simultaneously perpetuate exclusion and enable transformation. It also offers policy implications, calling for holistic, systemic strategies to address persistent gender disparities in entrepreneurship.